2022
DOI: 10.3390/jcm11123258
|View full text |Cite
|
Sign up to set email alerts
|

Durlobactam in the Treatment of Multidrug-Resistant Acinetobacter baumannii Infections: A Systematic Review

Abstract: A. baumannii is a frequent cause of difficult-to-treat healthcare-associated infections. The use of a novel beta-lactamase inhibitor, durlobactam, has been proposed against multidrug-resistant A. baumannii. A systematic review of studies assessing the efficacy and safety of durlobactam in the treatment of multidrug-resistant A. baumannii infections was carried out. The study protocol was pre-registered on PROSPERO (CRD42022311723). Published articles on durlobactam were identified through computerized literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Many nosocomial infections were treatable with medicines; however, the increase in AMR rate has resulted in favoring the use of wide-spectrum antimicrobials in clinical practices, which in turn could lead to antimicrobial selection effects, conversely, this made it challenging to treat AB-infected patients. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nosocomial infections were treatable with medicines; however, the increase in AMR rate has resulted in favoring the use of wide-spectrum antimicrobials in clinical practices, which in turn could lead to antimicrobial selection effects, conversely, this made it challenging to treat AB-infected patients. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Many nosocomial infections were treatable with medicines; however, the increase in AMR rate has resulted in favoring the use of wide-spectrum antimicrobials in clinical practices, which in turn could lead to antimicrobial selection effects, conversely, this made it challenging to treat AB-infected patients. 46,47 The results of phenotypic AMR profiling showed that the resistance rate of MDR-AB to cephalosporins and carbapenems was higher than aminoglycosides, fluoroquinolones, tigecycline, and cefoperazone-sulbactam sodium. 48 The analysis of clinical diagnosis and antibiotics used in the infected patients revealed that the most used antimicrobial drug in clinical practice was the enzyme-inhibitor complex (cefoperazone-sulbactam sodium or piperacillin-sulbactam), followed by the combined application of two or more antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the eleven SUL–DUR-resistant A. baumannii we found Q488K and Y528H mutations in PBP3. To date, reports of SUL–DUR resistance have been rare and resistance is usually attributed to the presence of metallo-β-lactamases, which DUR does not inhibit, or to mutations near the active site of PBP3, the target of sulbactam [ 24 , 25 , 26 ]. Few therapeutic choices are available to treat CR Ab isolates [ 14 , 16 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Durlobactam (DUR), previously called ETX2514, is a non-β-lactam diazabicyclooctane (DBO) inhibitor with activity against Ambler class A, C and D β-lactamases [ 22 , 23 ]. Recently, some studies have shown that sulbactam in combination with durlobactam is active against MDR A. baumannii [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Sulbactam (SUL) is one of the first β-lactamase inhibitors used in combination with ampicillin for the treatment of class A β-lactamase-producing pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…SUL/DUR was approved in May 2023 for adult patients with hospital-acquired bacterial pneumonia and ventilator-associated pneumonia caused by susceptible AB isolates, following the ATTACK trial [108 ▪ ,109 ▪▪ ]. The ATTACK trial showed that SUL/DUR was more effective than Colistin, with a lower mortality rate and less nephrotoxicity.…”
Section: What Is the Current Role Of Sulbactam And Sulbactam Combinat...mentioning
confidence: 99%